Percepções de portadores de hanseníase sobre a doença, seu tratamento e as repercussões em seu ambiente: um estudo no município de Nossa Senhora do Socorro - Santos, Vania Carvalho (2006)
Leprosy (or Hnasen’s Disease), is a major problem in Brazillian public health not only for its prevalence rate of cases but also for its chronic development. Futhermore, when the disease is not treated, it may cause injuries and deformities. The objective of developing this research was due to permanent cases of this ailment in Nossa Senhora do Socorro, a small town in Sergipe. This city ranks in the third position concerning the incidence of the disease in the state of Sergipe. The public heath institutions claim that prejudice and exclusion of part of the population to have access diagnosis and treatment even in the beginning of the disease have been the main obstacles to eliminate leprosy. The general purpose of the research was to find out and analyze the leprosy patients in order to know the sufferers’ profile in terms of socioeconomic aspects, information about the disease, ways of treatment and the impact of the disease in the leprosy patients’ everyday life. The methodological procedures combined documentary analysis and semistructured interview. The group involved in the research was maily women still working with low family’s income and poor schooling, bad jobs. It is important that these patients didn’t have correct information about either the diagnosis or the beginning of the treatment, for they ended up mixing up the symptoms of leprosy with other diseases, sometimes they couldn’t even notice them. Although they had undergone the treatment, some had wrong interpretation and consequently stopping the treatment. In relation to the impacts in the sufferers’ everyday life, it could be noticed negative repercussion in their self image, willingness of occultation of the disease and the perception of healing as the elimination of all symptoms and sequels. It can be concluded through the research that prevention, diagnosis and treatment can’t be limited to health area only, but it is important to mention the necessity of involving health, education and environment. Last but not least, it is worth mentioning enviromental education, as well as taking into consideration the patients’ insights and their living conditions to promote the prevention and treatment of the disease.